Associations of deviant peer affiliation with youths' substance use disorder abstention motivation: The mediating role of perceived social support and the moderating role of collective identity. Issue 2 (2nd May 2022) - Zeng, Xiaoqing; Chen, Yuling
Abstract: The aim of the current study is to explore the mechanism by which deviant peer affiliation affects substance abusers' substance abstention motivation and the mediating role of perceived social support in the relationship between these concepts. Moreover, we also investigated whether collective identity moderates the relations among deviant peer affiliation, perceived social support, and substance rehabilitation. The participants were 430 male substance abstainers who completed a battery of questionnaires. The Chinese versions of the Deviant Peer Affiliation Questionnaire, Motivation for Abstention Scale, Perceived Social Support Scale and Identity Orientation Scale were used. The results showed that all the dimensions of deviant peer affiliation were negatively associated with the dimensions of substance abstention motivation. Moreover, perceived social support partially mediated the relations between deviant peer affiliation and substance abstention motivation. Additionally, collective identity was a significant moderator of the relations between perceived social support and substance abstention motivation. These findings provide a clearer understanding regarding the impact of deviant peer affiliation and perceived social support on substance abstention motivation in individuals with substance use disorder.